A 66‐bp deletion in growth hormone releasing hormone gene 5′‐flanking region with largemouth bass recessive embryonic lethal. (3rd April 2014) - Ma, D. M.; Han, L. Q.; Bai, J. J.; Li, S. J.; Fan, J. J.; Yu, L. Y.; Quan, Y. C.
Summary Growth hormone releasing hormone (GHRH) regulates the secretion of growth hormone (GH) in the pituitary gland. A 66‐bp deletion (c.‐923_‐858del) was detected in the 5′‐flanking sequence of the largemouth bass (Micropterus salmoides) GHRH gene. In two cultured random populations of adult individuals (A: n = 170 and B: n = 150), the genotype ratios of +/+:+/− were 2.5:1 and 2.8:1 respectively. Only one −/− fish was detected. A Largemouth bass family was constructed with two heterozygous individuals (+/−) as parents. The genotype ratio of +/+:+/−:−/− in the filial generation embryos was 1:1.6:0.1 at the neurula and 1:2:0 at hatched larvae stages. This indicated that the 66‐bp deletion was a recessive lethal site and that homozygous individuals (−/−) died off in embryonic development. The growth traits (body weight, body length and body depth) were measured, and the GHRH mRNA expression levels in brain tissue were detected using real‐time PCR. The effects of genotype (+/−) on growth traits and GHRH mRNA expression were not significant. Although the cause of death was not clear, the results hint that the 66‐bp deletion site in GHRH 5′‐flanking sequence significantly affects the livability in largemouth bass embryonic development.